A novel MPPT PI discrete reverse-acting controller for a wind energy conversion system. (November 2021) - González-Hernández, José Genaro; Salas-Cabrera, Rubén; Vázquez-Bautista, Roberto; Ong-de-la-Cruz, Luis Manuel; Rodríguez-Guillén, Joel
Abstract: This paper presents an original maximum power point tracking controller for an experimental direct-drive full-variable-speed full-rated converter Type IV Wind Energy Conversion System in standalone operation. Specifically, we propose and implement in a real-time platform a novel reverse-acting controller that is strongly aimed at obtaining reliable and efficient experimental results to extract maximum power from the wind. Since our approach is focused on the experiments, we purposely derive a concise control law that can easily be implemented using a standard digital processor. Our initiative is presented as an alternative to some recent and valuable proposals that are based on detailed models that may be difficult to implement. An open-loop steady-state analysis is also presented in order to demonstrate the reverse-acting relationship between the input and output of the system to be controlled. Graphical abstract: Image 1 Highlights: A novel controller is proposed for a permanent magnet-based wind energy system. An open loop steady state analysis supports the reverse acting characteristic. Experimental results demonstrate that maximum power is extracted from the wind. A concise control law is derived so it can be implemented in a standard processor. Real wind speed data are used to demonstrate MPPT performance.